Public spending and growth: the role of government accountability - Morozumi, Atsuyoshi; Viega, Francisco José (Elsevier, 2016)
This paper examines the role of institutions in the nexus between public spending and economic growth. Empirical results based on a newly assembled dataset of 80 countries over the 1970-2010 period suggest that particularly when institutions prompt governments to be accountable to the general citizen does public capital spending promote growth. Taking account of the type of financing for this spending, we show that the growth promoting effect under an accountable government appears to prevail for various financing sources, including a reallocation from current spending, an increase in revenue, and a rise in the budget deficit. However, government accountability does not seem to play a key role in the growth effects of current spending.